Spatial distribution of rotavirus in calves in the state of São Paulo, Brazil: 2006 to 2010 - Heloisa Pinto de Godoy; Ingrid Bortolin Affonso Lux Hoppe (Agro@mbiente On-line)
Rotavirus is the major causative agent of diarrhea in animals and humans; it causes economic burden and negatively impacts public health. A striking feature of this virus is the genotypic diversity of circulating strains. The objective of the present study was to identify the geographical distribution of rotavirus in the State of São Paulo, Brazil, in bovine species between 2006 and 2010. This investigation was performed in the Rotavirus Laboratory of the Faculty of Agrarian and Veterinary Sciences of the Paulista State University “Júlio de Mesquita Son “(Unesp). Maps were constructed using commercially available software (MapInfo Pro version 7.5, Pitney Bowes, Stamford, CT, USA) to analyze spatial distribution. A total of 803 fecal samples obtained from calves from 48 herds of dairy and beef cattle from 21 different municipalities were analyzed. The samples were characterized using polyacrylamide gel electrophoresis (PAGE) tests. The PAGE test revealed rotavirus-positive animals in 33.3% (16/48) of the herds, with 6.1% (49/803) of the analyzed samples testing positive. Of the 15 municipalities in which dairy herds were analyzed, 46.7% (7/15) had rotavirus-positive samples: Araçatuba, Cajobi, Descalvado, Guariba, Pontalinda, Taiaçu, and Votuporanga. For beef cattle, 22.8% (26/114) of the samples were diagnosed to be positive, 21% (3/13) of which were from herds. Positive samples were found in 42.8% (3/7) of the cities including Araçatuba, Catiguá, and Fernandópolis. Identification of rotavirus infection is of great value because the virus is disseminated throughout several localities in the State of São Paulo that exhibit different environmental characteristics and forms of production.